Dual optimization approach to Mo single atom dispersed g-C3N4 photocatalyst: Morphology and defect evolution - Zhang, Chen; Qin, Deyu; Zhou, Yin; Qin, Fanzhi; Wang, Hou; Wang, Wenjun; Yang, Yang; Zeng, Guangming (Applied catalysis. B, Environmental, 2022)
Reasonable regulation of the interaction between metal center and the ligand to achieve a high-density atomic loading without agglomeration has been the formidable challenge to the development of single-atom catalysts (SACs). Herein, an advanced photocatalyst based on N-vacancy (Nv) tubular porous g-C3N4 (TCN) decorated with atomically dispersed Mo (Mo/Nv-TCN) is synthesized. The large specific surface area of the tubular morphology contributes to suppress the agglomeration of Mo atoms, while the N defect induces the formation of specific stable Mo-2 C/2 N configuration between the light absorbers and the Mo sites. As the active center of the photocatalytic reaction, single Mo atom causes the directional transfer of local charges on the surface of the support, while the Mo-2 C/2 N bond acts as a bridge for photoexcited charge transfer. As a result, the precisely designed Mo SACs system shows remarkable photoelectric properties and renders excellent photocatalytic performance for tetracycline (TC) degradation under visible light irradiation. [Display omitted] •The photocatalyst based on N-deficient tubular porous g-C3N4 (Nv-TCN) decorated with single atom Mo is synthesized.•The precise control of single atom Mo on the surface of the carrier is realized by morphology and defect engineering.•Advanced characterizations and DFT calculations confirm the formation of the Mo-2 C/2 N coordination structure.•The Mo atom and Mo-2C/2N bonds act as active site and electron transfer bridges, respectively.•The precisely designed Mo SACs system shows remarkable photoelectric properties.